Lifting posterior mitral annuloplasty for enhancing leaflet coaptation in mitral valve repair: midterm outcomes - Song, Meong Gun; Shin, Je Kyoun; Chee, Hyun Keun; Kim, Jun Seok; Yang, Hyun Suk; Choi, Jong Bum (Annals of Cardiothoracic Surgery, 2015)
Background: We evaluated the midterm outcomes of lifting posterior mitral annuloplasty for enhancing leaflet coaptation in mitral valve repair. Methods: Between October 2007 and December 2012, 341 consecutive patients with significant mitral regurgitation underwent lifting posterior mitral annuloplasty using a specially designed fabric annuloplasty strip that lifts the middle portion of the posterior annulus. Associated procedures for mitral valve repairs, such as patch valvuloplasty for posterior leaflet prolapse (n=80), new chord placement for anterior leaflet prolapse (n=33), commissurotomy (n=29), and posterior leaflet extension (n=23), were performed in 141 patients (41.3%). Results: Thirty-day mortality was 0.9%. Nine late deaths (2.6%) occurred. Mean overall survival at 5 years was 96.0%±1.1%. During the mean follow-up period of 38±17 months, six patients (1.8%) underwent valve-related reoperation (5-year freedom from valve-related reoperation, 98.1%±0.8%). At 5 years, mean freedom from recurrence of mitral regurgitation grade 3+ to 4+ (moderate to severe) was 95.1%±1.6%. The mean valve pressure gradient (PG) was 3.2±1.5 mmHg across all strip sizes at the time of follow-up. Conclusions: Lifting posterior mitral annuloplasty using an innovative annuloplasty strip in mitral valve repair has a low rate of recurrent regurgitation or valve-related reoperation with rare relevant complications.